Measurment of The Effect of Sample Thickness on Absorption of Microwaves - Abdalhadi, Daw Mohammad (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
This study investigated the effect of sample thickness on microwave absorption for a material composed of polylactic acid (PLA) and oil palm empty fruit bunch (OPEFB) fiber. The sample was prepared with 30% oil palm fiber and 70% PLA polymer. A network analyzer (model N5227) was used to measure the sample’s electrical permittivity, with the real part recorded as 2.845 and the imaginary part as 0.216. Additionally, the COMSOL simulation program was employed to examine the electric field distribution in the samples and calculate the transmission coefficient (S₂₁) and reflection coefficient (S₁₁) for electromagnetic waves in the microwave frequency range of 8-12 GHz. The transmission coefficient (S₂₁) values ranged from 0.729 to 0.950, while the reflection coefficient (S₁₁) values varied between 0.199 and 0.657 at a frequency of 10 GHz, expressed in decibels.